The Influence of Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Operating Costs to Operating Income (BOPO) on Liquidity as Measured by Loan to Deposit Ratio at Bank Rakyat Indonesia Tbk - Amir Makhmud Zain Nst; Siti Wardah Pratidina Nst; Dicky Pratama (ProBisnis : Jurnal Manajemen, 2020)
The purpose of this research is to analyze and test the effect of CAR, NPL, BOPO on the LDR of PT. Bank Rakyat Indonesia Tbk. This type of research is explanatory research. The sample used in this research is PT. Bank Rakyat Indonesia Tbk which published its financial statements for the period 2006-2013. Data collection techniques are library research and field research. This study uses descriptive analysis, classical assumption test and multiple linear regression for data analysis with the help of the Eviews 8 program. From the analysis test results it is known that the CAR, BOPO and NPL ratios have an effect on the LDR ratio during the 2006-2013 period